Linking Creativity, Environment, and Capital to Entrepreneurial Intention Through Motivation - Bekti Utomo; Rohmawan Adi Pratama; Wahyu Agung Setyo; Eva Yuniarti Utami; Novi Ria Rahmawati; Merlin Swantamalo Magna; Dama Yuninata; Lastika Ary Prihandoko (Universitas Negeri Makassar, 2025)
This study examines the effects of creativity, environment, and capital on entrepreneurial intention, with motivation serving as a mediating variable. A quantitative approach was employed using survey data collected through questionnaires distributed to respondents selected by proportional random sampling. The study involved 109 respondents drawn from the target population in a higher education context. The data were analyzed to assess both the direct and indirect relationships among the proposed variables. The findings indicate that motivation has a significant direct effect on entrepreneurial intention and functions as the main mediating variable in the model. Creativity has a positive effect on motivation and contributes substantially to entrepreneurial intention through motivation. The environment also shows the strongest positive contribution to both motivation and entrepreneurial intention, while the effect of capital on entrepreneurial intention appears weaker than the other predictors. Overall, the model explains a substantial proportion of the variance in entrepreneurial intention, highlighting the central role of motivation in connecting individual, environmental, and resource-related factors to entrepreneurial outcomes. These findings suggest that efforts to strengthen entrepreneurial intention should not focus solely on financial resources, but also on fostering creativity, supportive environments, and stronger motivational readiness. The study offers practical implications for higher education institutions in designing entrepreneurship development programs that integrate personal capability, environmental support, and motivational reinforcement.